2022
DOI: 10.3399/bjgpo.2021.0204
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk in remote consultations in general practice: findings from in-COVID-19 pandemic qualitative research

Abstract: BackgroundThe Covid-19 pandemic-related rise in remote consulting raises questions about the nature and type of risks in remote general practiceAimTo develop an empirically-based and theory-informed taxonomy of risks associated with remote consultations.Design and settingQualitative sub-study of data selected from the wider datasets of three large, multi-site, mixed-method studies of remote care in general practice prior to and during the Covid-19 pandemic in the UKMethodSemi-structured interviews and focus gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 14 publications
5
37
0
Order By: Relevance
“…These simplistic, polarised narratives around modes of consulting were not helped by a commodification of clinical care (patients were depicted as customers who had a right to see the GP in person). The reality of clinical diagnosis and management is, of course, far more nuanced, with multiple interacting influences contributing to safe and effective clinical care and the balancing of good care and patient satisfaction (4,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…These simplistic, polarised narratives around modes of consulting were not helped by a commodification of clinical care (patients were depicted as customers who had a right to see the GP in person). The reality of clinical diagnosis and management is, of course, far more nuanced, with multiple interacting influences contributing to safe and effective clinical care and the balancing of good care and patient satisfaction (4,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst our own in-pandemic research found examples of high-quality remote care [8][9][10] , we affirmed these concerns and identified six new kinds of risk: a) practice organisation and set-up (digital inequities which restricted access, technologies that were unreliable and unfit for purpose, and reduced service efficiency); b) communication and the therapeutic relationship (a shift to more transactional consultations); c) quality of clinical care (including missed diagnoses, safeguarding challenges, over-investigation and over-treatment); d) increased burden on the patient (e.g. to self-examine and navigate between services); e) fewer opportunities for screening and managing the social determinants of health; and f) adverse impact on workforce (clinician and staff stress and compromised learning) 21,22 .…”
Section: Remote General Practice During the Pandemicmentioning
confidence: 99%
“…Remote care may compromise the therapeutic relationship and continuity of care 19,20 , lead to more transactional forms of clinical interaction 22 , fewer ' doorknob consultations' 15 , and delayed diagnosis of serious illness 75,76 ; it may be unsuitable for those with complex needs [20][21][22] . Remote reviews may be convenient and safe for patients with stable long-term conditions 77 .…”
Section: Quality and Safety Of Carementioning
confidence: 99%
“…A government policy of 'remote-by-default' care introduced in July 2021 10 was reversed a few months later 11 because it was unpopular with patients and concerns had emerged about quality and safety (e.g. missed diagnoses, safeguarding challenges, over-investigation, over-treatment, and threats to the therapeutic relationship), digital inequalities, increased burden on the patient, and increased staff workload and stress 12,13 .…”
Section: Introductionmentioning
confidence: 99%